Nephroblastoma in infants, 1969-75: variations in treatment and survival. Issue 6250 (8th November 1980) - Stiller, C A; Lennox, E L
Abstract : In a series of 79 infants aged under 1 year with nephroblastoma diagnosed during 1969-75 all the patients underwent nephrectomy, 33 (42%) received a course of radiotherapy, and 49 (62%) received chemotherapy. The overall three-year survival rate for patients who survived at least one week after diagnosis was 65%. The corresponding rate for infants with stage I tumours was 76%. The survival rate in children with early-stage tumours was significantly higher in those who were treated by nephrectomy and chemotherapy alone compared with those who also received radiotherapy. In a large proportion of cases nephrectomy and chemotherapy together constituted sufficient treatment for the cure of infants with nephroblastoma, and in some instances nephrectomy alone proved adequate. There was no general tendency for children under 1 year old to be unable to withstand chemotherapy.